Traditional method or online teaching; which method students prefer: an observational study - Gayatri, B. S. S. N. V. R.; Kishore, S. Ravindra; Surekha, Teki; Triveni, Vanimina (International Journal of Research in Medical Sciences, 2022)
Background: An unexpected global pandemic broke out in initial months of 2020 i.e., COVID-19 which drastically brought a difference in the progress of education in various institutions, especially the medical field where we study about life was also made online. This study aims to conduct a comparative analysis of students ‘opinion regarding which is the better, traditional teaching or online live teaching. Methods: Survey was conducted among two group of students, 2019 (both online and offline teaching) and 2020 (online teaching with offline practical) batches of Andhra Medical College, Visakhapatnam. A questionnaire was circulated to students regarding the class experience, interest of attending the class, learning effect and clarity of the lecture. Results: Students expressed their views that overall teaching experience and learning effect of offline methodology is superior to online approach, so the traditional offline style or the blend of online and offline modes are apt for teaching. Conclusions: The study is focused on the way in which the teaching and learning approach is delivered which is favoured by the medical practitioners, the qualitative data suggesting required modifications for further improvement in the delivering method to produce qualified medical practitioners to meet the current and imminent situations. This study suggests that a intermingled learning approach is an effective method for anatomy learning, and this approach mainly inculcates self-directed study through online learning.